ANALISIS DEBIT BANJIR PADA SUB DAERAH ALIRAN (DAS) SUNGAI TABUK, PERBANDINGAN METODE HIDROGRAF SATUAN SINTETIK SCS DAN SNYDER - Nilna Amal; Noor Haliza (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2025)
Floods are a natural disaster that can occur during the rainy season in various watershed areas across many regions of Indonesia. Continuous heavy rainfall causes rivers to exceed their capacity, leading to flooding. The Sungai Tabuk sub-district, which comprises 20 villages and one urban village, is entirely affected by flooding, with the worst-hit area being Pemakuan Darat Village. To determine the magnitude of the flood discharge, a hydrological model simulation using the HEC-HMS software is necessary. The analysis was conducted by collecting data on the Sub-basin of Sungai Tabuk, which includes primary and secondary data. The data was processed to create a rainfall-runoff model using HEC-HMS. The rainfall distribution process was carried out using the Mononobe distribution. The method used is the SCS Curve Number, while direct runoff is analyzed using the HSS SCS and the HSS Snyder. The simulation results with observations dated January 1, 2021, using the Mononobe distribution method by SCS and Snyder, are as follows: the SCS method at the outlet Reach and Sink had the highest discharge of 1,430.2 m³/s, whereas the Snyder method had a discharge of only 1,092.3 m³/s. In contrast, the discharge observed in the field was 39.072 m³/s. It can be seen that the discharge values from the HEC-HMS software are significantly higher than the discharge values obtained in the field.